Utilization of waste empty palm oil bunches as a medium for seeding and nursery for UNIB hybrid chilies - Mujiono Mujiono; Evi Andriani; Andwini Prasetya; Eko Sumartono; Dwi Wahyuni Ganefianti; Endang Sulistyowati; Agustin Zarkani (Community Empowerment, 2023)
Lawang Agung Village is situated in Air Periukan District, Seluma Regency, directly adjacent to plantation land owned by PT. Agri Andalas. Waste empty palm fruit bunches (TKKS) or 'jangkos' are an organic compost that can support plant growth. This community service aims to provide training and practical experience in seeding and breeding UNIB hybrid chilies using jangkos compost as an organic medium. In its implementation, activities begin with training, preparing seeds, tools, and materials. They then continue with seeding and nursery practices involving 20 PKK cadres. The hybrid chilies sown include the UNIB Pi, P3, P5, and P7 hybrid chilies. On November 28, the seedlings, which were 34 days old, were transplanted into polybags measuring 40 x 40 cm in the village nursery. Based on the activity evaluation, the partners demonstrated an understanding of the process of seeding and breeding UNIB hybrid chilies and successfully used jangkos as a planting medium.